Communication Activities on the Implementation of E-procurement in Indragiri Hulu Regency - Muhd Ar. Imam Riauan; Yerli Sitanggang; Zeti Azreen Ahmad (Journal of Applied Engineering and Technological Science (JAETS), 2022)
This study aims to understand communication activities in implementing E-procurement in Indragiri Hulu Regency. This research is interesting in understanding communication activities in the implementation process in frontier, outermost, and underdeveloped (3T) regions. E-Procurement is an application for managing goods/services procurement data, including internet-based procurement data, designed to achieve an effective, efficient, and integrated procurement process. This research is qualitative research to explore communication activities in implementing E-Procurement. The subjects of this study amounted to 8 people involved in the Implementation of e-procurement. Data analysis was carried out in three steps: data reduction, data presentation, and conclusion. The study results show that communication activities occur in 4 stages of the auction process carried out by the Electronic Procurement Agency. This process involves regional apparatus organizations in Indragiri Hulu Regency with suppliers who provide goods and services registered in the electronic procurement system in Indragiri Hulu Regency. The process of procuring goods starts with a proposal process from each Regional Apparatus Organization based on their respective Performance Plans to carry out the bidding process. The auction process is carried out by a working group team formed by the Head of LPSE, which suppliers of goods and services will follow. The Working Group team will evaluate the documents proposed by the supplier and determine the tender winner.